+0  
 
+1
84
2
avatar

Completely factor the following expression: 

(9x^5 + 25x^3 - 4) - (x^5 - 8x^3 - 4)

 Apr 4, 2021
 #1
avatar+18 
+1

(9x^5+25x^3- 4) - (x^5 - 8x^3 - 4) = (9-1)x^5 + (25+8)x^3 + (-4+4) = 8x^5 + 33x^3

 Apr 4, 2021
 #2
avatar+320 
+2

Hey there, Guest!

 

So, first, we need to distribute the negative sign:

\(=9x^5+25x^3−4+−1(x^5−8x^3−4)\)

\(=9x^5+25x^3+−4+−1x^5+−1(−8x^3)+(−1)(−4)\)

\(=9x^5+25x^3+−4+−x^5+8x^3+4 \)

 

Then, we can combine like terms:

\(=9x^5+25x^3+−4+−x^5+8x^3+4\)

\(=(9x^5+−x^5)+(25x^3+8x^3)+(−4+4)\)

\(=8x^5+33x^3\)

 

In case you missed that, the answer is:

\(=8x^5+33x^3\)

 

Hope this helped! :)

( ゚д゚)つ Bye

 Apr 4, 2021

10 Online Users